2018
DOI: 10.7554/elife.30649
|View full text |Cite
|
Sign up to set email alerts
|

FoxP2 isoforms delineate spatiotemporal transcriptional networks for vocal learning in the zebra finch

Abstract: Human speech is one of the few examples of vocal learning among mammals yet ~half of avian species exhibit this ability. Its neurogenetic basis is largely unknown beyond a shared requirement for FoxP2 in both humans and zebra finches. We manipulated FoxP2 isoforms in Area X, a song-specific region of the avian striatopallidum analogous to human anterior striatum, during a critical period for song development. We delineate, for the first time, unique contributions of each isoform to vocal learning. Weighted gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 67 publications
(124 reference statements)
0
35
0
Order By: Relevance
“…Similarly, FOXP1 and FOXP2 mutations in humans lacking the FKH can lead to truncated proteins that do not localize to the nucleus (MacDermot et al, ; Vernes et al, ; Mizutani et al, ; Lozano, Vino, Lozano, Fisher, & Deriziotis, ). A recent study on zebra finches revealed that overexpression of an FKH‐lacking FoxP2 isoform in a brain nucleus important for song‐learning led to differences in the acoustic features and variability of the adult song (Burkett et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, FOXP1 and FOXP2 mutations in humans lacking the FKH can lead to truncated proteins that do not localize to the nucleus (MacDermot et al, ; Vernes et al, ; Mizutani et al, ; Lozano, Vino, Lozano, Fisher, & Deriziotis, ). A recent study on zebra finches revealed that overexpression of an FKH‐lacking FoxP2 isoform in a brain nucleus important for song‐learning led to differences in the acoustic features and variability of the adult song (Burkett et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Area X: Miller et al. – 7–10 birds; Heston and White – 7–10 birds; Goldberg and Fee – 7–12 birds; Burkett et al., – 7 birds). We thus used 7–9 birds per DREADDs construct (inclusive of HSV and AAV) for Area X experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we newly integrate those prior findings of behaviourally relevant gene co-expression modules in Area X of juvenile birds [9] with findings published by Pfenning et al [3], who identified gene expression patterns that are conserved in the brains of humans and song-learning birds. Specifically, the authors analysed transcriptomes from multiple brain regions from humans and song-learning birds (zebra finch, parrot and hummingbird) as well as vocal non-learning birds (dove and quail) and a non-learning primate species (macaque).…”
Section: (B) a Role For Endocannabinoids In Vocal Learningmentioning
confidence: 69%
“…Briefly, we found modules of genes whose co-expression was up-or downregulated by the amount of song that birds sang on the morning of the experiment. Strikingly, these 'song modules' were specific to Area X and observed in both adults and juveniles, speaking to the profound influence of singing behaviour on the transcriptome [9,10]. Excitingly, the analysis shows modules correlated to the amount of tutor song learning by a pupil, and these were restricted to juveniles.…”
Section: (B) a Role For Endocannabinoids In Vocal Learningmentioning
confidence: 87%
See 1 more Smart Citation